Proyecto de Factibilidad para la creación de un Laboratorio de Gastronomia, Aplicando Sistemas de Calidad Certificados, para la Escuela de Gestión Turistica y Hotelera de la Universidad Nacional de Chimborazo. - Heredia Avalos, Jessica Isabel (2013)
The present Feasible Project it has carried out after the problematic raised by the school Tourist and Hotel Management, is so it has been thought about the creation of a Laboratory of Gastronomy, which is consolidated as a real tool of work both for the students and for the teachers, bringing together comfort and dynamism, since the existing laboratory does not offer these comforts. The need to do this project is in order that the students see this alternative as a new horizon to sustain his studies, since it is of general knowledge that the presentation of Gastronomic Festivals or the preparation of coffee breaks they have served us for the accomplishment of several activities both in ends of knowledge and in ends of personal profit, giving this way a new alternative of sustenance to the student.